Caribbean Report 09-08-1988 - Timmins, Jerry (anchor); Robinson, A.N.R. (interviewee); Taylor, Jeremy (correspondent); Hewin, Sarah (interviewee); Crosskill, Hugh (correspondent); Elliot, Michael (interviewee) (The British Broadcasting Corporation, 1988)
This program reports on the political climate in Trinidad and Tobago in the wake of the split in the National Alliance for Reconstruction (NAR) Coalition, and the formation of a new political party known as Club 88. The program also takes a look at the state of the economy of Trinidad and Tobago and the tough political and economic issues facing the A.N.R Robinson administration. Finally, BBC correspondent Hugh Crosskill examines the atmosphere at cricket grounds during test matches between the West Indies and England. The contentious issue of West Indies supporters’ exuberance and the level of noise that they make during the matches is discussed, along with measures taken to control the noise.
1. Headlines: (Jerry Timmins) (00:27-00:47)
2. Alan Tomlinson reports on the breakup of the coalition government in Trinidad and Tobago which was formed by the National Alliance for Reconstruction (NAR) and the formation of a new political party by the dissidents, which was dubbed “Club 88”. The segment includes a brief comment by Trinidad and Tobago Prime Minister A.N.R. Robinson. (00:51-03:50)
3. BBC correspondent Jeremy Taylor reports on the state of the Trinidad and Tobago economy and the many critical economic issues facing the Robinson administration. He also comments on the government’s optimistic, medium-term economic plan. (03:52-05:57)
4. Financial News: (Pat Whitehorn) This segment includes comments by Sarah Hewin, an economist at American Express Bank. (06:03-07:29)
Keywords: Political parties-- Trinidad and Tobago.; Economics -- Trinidad and Tobago.; Cricket fans -- England.; National Alliance for Reconstruction (Trinidad and Tobago)